First report of Cryptosporidium andersoni and risk factors associated with the occurrence of Cryptosporidium spp. in pre-weaned native Korean calves with diarrhea - Jang, Dong-Hun; Cho, Hyung-Chul; Park, Yu-Jin; Park, Jinho; Choi, Kyoung-Seong (Frontiers in Veterinary Science, 2023)
Cryptosporidium spp. are important enteric protozoan parasites that infect humans and other animals throughout the world. Cryptosporidium infection in cattle industry leads to substantial economic losses due to diarrhea, growth retardation, weight loss, and possibly death. Most studies have focused on C. parvum, and studies on other Cryptosporidium spp. and calf diarrhea are limited. Therefore, this study aimed to investigate the occurrence of Cryptosporidium spp. in pre-weaned calves, to determine the risk factors for Cryptosporidium spp. infection such as age and season, and to identify subtypes of C. parvum circulating in the Republic of Korea (ROK). A total of 510 fecal samples were collected from calves with diarrhea and divided by age and season. Cryptosporidium spp. were first screened using PCR targeting the small subunit (SSU) rRNA gene and further the 60-kDa glycoprotein gene for subtyping of C. parvum. Out of 510 fecal samples, 71 (13.9%) were positive for Cryptosporidium spp. in pre-weaned calves with diarrhea. C. andersoni (2.8%), C. bovis (30.9%), C. parvum (29.6%), and C. ryanae (36.6%) were identified. C. ryanae was the most predominant in calves in the ROK. Calf age was a significant risk factor for C. bovis (2=13.83, P=0.001), C. parvum (2=7.57, P=0.023), and C. ryanae (2=20.18, P=0.000) occurrence. Additionally, C. parvum was detected 3.1-fold more frequently in pre-weaned calves with diarrhea in fall (95% CI: 1.237.81; P=0.016) than in spring, whereas C. ryanae was 8.9-fold more frequently detected in summer (95% CI: 1.6548.68; P=0.011) than in spring. Three subtypes (IIaA17G4R1, IIaA18G3R1, and IIaA20G3R1) of C. parvum were identified. Of them, IIaA17G4R1 was the most common, whereas IIaA20G3R1 was not previously detected in calves in the ROK. To our knowledge, this is the first report of C. andersoni in pre-weaned calves in the ROK. The occurrence of Cryptosporidium spp. appears to be age-dependent in calves. Season had a significant effect on the occurrence of C. parvum and C. ryanae. Taken together, C. bovis and C. ryanae along with C. parvum are detected in pre-weaned calves with diarrhea and these two pathogens should not be overlooked in the diagnosis of calf diarrhea.